Differences in Adiponectin Gene Expression: Adiponectin Gene Expression is Higher in Gluteal than in Abdominal Adipose Tissue - Moghadasi, Mehrzad; Mohebbi, Hamid; Rahmani-Nia, Farhad; Hassan-Nia, Sadegh; Noroozi, Hamid; Nematollahzadeh, Mohadeseh (Asian Journal of Medical Sciences, 2013)
Objective: Obesity down regulated the adiponectin gene expression, but differences in adiponectin gene expression in gluteal adipose tissue (GAT) and in abdominal adipose tissue (AAT) are not well known. Therefore, the purpose of this study was to examine the differences in adiponectin gene expression in GAT and in AAT. Material & Methods: Nineteen healthy obese middle aged men (aged 41.4±6.1 years; mean ± SD) Adipose tissue (AT) biopsies from the subcutaneous abdominal and subcutaneous gluteal depots were obtained. Results: Adiponectin gene expression was 22.7% higher in subcutaneous GAT than in subcutaneous AAT. Conclusion: Adiponectin gene expression is higher in GAT than in AAT, suggesting GAT to be more important for circulating adiponectin levels. DOI: http://dx.doi.org/10.3126/ajms.v5i1.4412 Asian Journal of Medical Science Vol.5(1) 2014 pp.34-38